Anopheline mosquito saliva contains bacteria that are transferred to a mammalian host through blood feeding - Accoti, Anastasia; Damiani, Claudia; Nunzi, Emilia; Cappelli, Alessia; Iacomelli, Gloria; Monacchia, Giulia; Turco, Antonella; D’Alò, Francesco; Peirce, Matthew J.; Favia, Guido; Spaccapelo, Roberta (Frontiers in Microbiology, 2023)
Malaria transmission occurs when Plasmodium sporozoites are transferred from the salivary glands of anopheline mosquitoes to a human host through the injection of saliva. The need for better understanding, as well as novel modes of inhibiting, this key event in transmission has driven intense study of the protein and miRNA content of saliva. Until now the possibility that mosquito saliva may also contain bacteria has remained an open question despite the well documented presence of a rich microbiome in salivary glands. Here, using both 16S rRNA sequencing and MALDI-TOF approaches, we characterized the composition of the saliva microbiome of An. gambiae and An. stephensi mosquitoes which respectively represent two of the most important vectors for the major malaria-causing parasites P. falciparum and P. vivax. To eliminate the possible detection of non-mosquito-derived bacteria, we used a transgenic, fluorescent strain of one of the identified bacteria, Serratia marcescens, to infect mosquitoes and detect its presence in mosquito salivary glands as well as its transfer to, and colonization of, mammalian host tissues following a mosquito bite. Finally, we showed that Plasmodium infection modified the mosquito microbiota, increasing the presence of Serratia while diminishing the presence of Elizabethkingia and that both P. berghei and Serratia were transferred to, and colonized mammalian tissues. These data thus document the presence of bacteria in mosquito saliva, their transfer to, and growth in a mammalian host as well as possible interactions with Plasmodium transmission. Together they raise the possible role of mosquitoes as vectors of bacterial infection and the utility of commensal mosquito bacteria for the development of transmission-blocking strategies within a mammalian host.